Reduced Seasonal Coronavirus Antibody Responses in Children Following COVID-19 Mitigation Measures, The Netherlands - Sikkema, Reina S.; Bruin, Erwin de; Ramakers, Christian; Bentvelsen, Robbert; Li, Wentao; Bosch, Berend-Jan; Westerhuis, Brenda; Haagmans, Bart; Koopmans, Marion P. G.; Fraaij, Pieter L. A. (Viruses, 2023)
SARS-CoV-2 prevention and control measures did not only impact SARS-CoV-2 circulation, but also the timing and prevalence of other seasonal respiratory viruses. Especially in children, information on exposure and infections to seasonal coronaviruses as well as SARS-CoV-2 in the first year of the pandemic is largely lacking. Therefore, we set up a one-year serological survey in a large tertiary hospital in the Netherlands. We show that seasonal coronavirus seroprevalence significantly decreased in 2021 in children less than one year, most likely due to COVID-19 control measures. The SARS-CoV-2 seroprevalence in children and adolescents increased from 0.4% to 11.3%, the highest in adolescents. This implies higher exposure rates in adolescents as compared to the general population (>18 years old). It is clear that there have been significant changes in the circulation and subsequent immunity against most respiratory pathogens as a result of the mitigation measures. The implications on shorter as well as longer term are still largely unknown, but the impact of the SARS-CoV-2 pandemic and subsequent control measures will continue to affect the dynamics of other pathogens.